Spike and nsp6 are key determinants of SARS-CoV-2 Omicron BA.1 attenuation - Chen, Da Yuan; Chin, Chue Vin; Kenney, Devin; Tavares, Alexander H.; Khan, Nazimuddin; Conway, Hasahn L.; Liu, Guan Qun; Choudhary, Manish C.; Gertje, Hans P.; O’Connell, Aoife K.; Adams, Scott; Kotton, Darrell N.; et al. (Nature, 2023)
The SARS-CoV-2 Omicron variant is more immune evasive and less virulent than other major viral variants that have so far been recognized1–12. The Omicron spike (S) protein, which has an unusually large number of mutations, is considered to be the main driver of these phenotypes. Here we generated chimeric recombinant SARS-CoV-2 encoding the S gene of Omicron (BA.1 lineage) in the backbone of an ancestral SARS-CoV-2 isolate, and compared this virus with the naturally circulating Omicron variant. The Omicron S-bearing virus robustly escaped vaccine-induced humoral immunity, mainly owing to mutations in the receptor-binding motif; however, unlike naturally occurring Omicron, it efficiently replicated in cell lines and primary-like distal lung cells. Similarly, in K18-hACE2 mice, although virus bearing Omicron S caused less severe disease than the ancestral virus, its virulence was not attenuated to the level of Omicron. Further investigation showed that mutating non-structural protein 6 (nsp6) in addition to the S protein was sufficient to recapitulate the attenuated phenotype of Omicron. This indicates that although the vaccine escape of Omicron is driven by mutations in S, the pathogenicity of Omicron is determined by mutations both in and outside of the S protein.
CRIS-Team Scopus Importer:2023-02-24